2019
DOI: 10.1259/dmfr.20180250
|View full text |Cite
|
Sign up to set email alerts
|

Anexvivocomparative study of occlusal and proximal caries using terahertz and X-ray imaging

Abstract: Objectives: To examine the effectiveness of terahertz (THz) pulsed imaging (TPI) in comparison to intraoral photostimulable phosphor late (PSP) and cone beam CT (CBCT) for the detection of dental caries ex vivo. Methods: Newly extracted 32 human permanent teeth surfaces (16 with caries and 16 without caries) were serially sectioned mesiodistally and imaged by using four image sets as follows: (1) CBCT; (2) PSP; (3) THz movie video; and (4) THz static images. All images were evaluated twice separately by two ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…TPI has been found to be an interesting technique for dental tissue (enamel, dentine and pulp) discrimination because refractive index differences enable the three tissue regions to be identified [66,148,[214][215][216][217]. TPI is not the only possible technique for dental disease monitoring [218]: (i) visual caries examination, for example, loss of enamel translucency in the region between the contacting proximal surfaces of two adjacent teeth, (ii) X-ray imaging, (iii) electrical impedance measurements, (iv) ultrasound and (v) fluorescence-based methods [218,219] can also be adopted. However, many disadvantages can be assessed to some of these techniques: (i) is not possible at early detection stages, (i) and (ii) are difficult for posterior teeth, (ii) is potentially harmful for patients' health because it uses ionizing radiation.…”
Section: Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…TPI has been found to be an interesting technique for dental tissue (enamel, dentine and pulp) discrimination because refractive index differences enable the three tissue regions to be identified [66,148,[214][215][216][217]. TPI is not the only possible technique for dental disease monitoring [218]: (i) visual caries examination, for example, loss of enamel translucency in the region between the contacting proximal surfaces of two adjacent teeth, (ii) X-ray imaging, (iii) electrical impedance measurements, (iv) ultrasound and (v) fluorescence-based methods [218,219] can also be adopted. However, many disadvantages can be assessed to some of these techniques: (i) is not possible at early detection stages, (i) and (ii) are difficult for posterior teeth, (ii) is potentially harmful for patients' health because it uses ionizing radiation.…”
Section: Skinmentioning
confidence: 99%
“…However, many disadvantages can be assessed to some of these techniques: (i) is not possible at early detection stages, (i) and (ii) are difficult for posterior teeth, (ii) is potentially harmful for patients' health because it uses ionizing radiation. For these reasons, additional strategies for dental health monitoring, with a particular emphasis on diagnosis at an earlier stage of formation and the use of non-ionizing radiations, are widely requested [218].…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…TPI has been found to be an interesting technique for dental tissue (enamel, dentine and pulp) discrimination because refractive index differences enable the three tissue regions to be identified [66,148,[214][215][216][217]. TPI is not the only possible technique for dental disease monitoring [218]: (i) visual caries examination, for example, loss of enamel translucency in the region between the contacting proximal surfaces of two adjacent teeth, (ii) X-ray imaging, (iii) electrical impedance measurements, (iv) ultrasound and (v) fluorescence-based methods [218,219] can also be adopted. However, many disadvantages can be assessed to some of these techniques: (i) is not possible at early detection stages, (i) and (ii) are difficult for posterior teeth, (ii) is potentially harmful for patients' health because it uses ionizing radiation.…”
Section: Ex Vivo In Vivomentioning
confidence: 99%
“…Finally, in order to verify TPI validity and effectiveness in dental caries detection, Kamburo glu et al [218] compared TPI (static images and movie video) with common radiological techniques: intraoral photostimulable phosphor late (PSP) and cone beam CT (CBCT) for the detection of dental caries ex vivo [218][219][220]. They demonstrated that TPI shows good performances for caries identification, compared to the most used techniques, see Figure 9.…”
Section: Ex Vivo In Vivomentioning
confidence: 99%